Implant-supported removable partial dentures in the mandible: A 3–16 year retrospective study. Issue 2 (April 2017) - Jensen, Charlotte; Meijer, Henny J.A.; Raghoebar, Gerry M.; Kerdijk, Wouter; Cune, Marco S.
Abstract: Purpose: The purpose of this retrospective study was to assess performance, together with biological and technical complications, of implant-supported removable partial dentures (ISRPD) in mandibular Kennedy class I situations with implants placed in the anterior or posterior position. Methods: 23 subjects with two endosseous implants to support a bilateral-free-ending mandibular removable denture were examined. Eight subjects had implants in the premolar (anterior) region and 15 subjects implants in the molar (posterior) region. Biological and technical complications were recorded from the patients' medical record. Patients filled out a validated questionnaire regarding their appreciation of oral health related quality of life (OHIP-NL49) and a VAS score on overall satisfaction. Results: Over a mean follow-up period of 8 years (median 8 years, range 3–16 years) the cumulative implant survival rate was 91.7% (SE 0.05). Mean peri-implant bone loss was 0.9 mm (SD 1.0 mm). Scores for bleeding on probing, plaque and mucosal health were generally low, but significantly worse for posteriorly placed implants. Significantly more biological complications occurred in the posterior group ( X 2 (1) = 3.9; p  = 0.048). In 65% of the cases no technical complications were registered. Mean overall OHIP score was 16.1 (SD 18.4) and patients were highly satisfied (VAS: 8.4; SD 2.1). Conclusions: Within the limitations of this retrospective study, in case of a Kennedy class I situation in the mandible, an ISRPD is a viable treatment option with a high implant survival rate and satisfied patients after a maximum of 16 years. Technical and biological complications should be anticipated. Anteriorly placed implants performed slightly better.